Investigating the mechanism of rough phenotype in a naturally attenuated Brucella strain: insights from whole genome sequencing - Han, Wendong; Wei, Dong; Sun, Zhiping; Qu, Di (Frontiers in Medicine, 2024)
Objective: Brucellosis, a significant zoonotic disease, not only impacts animal health but also profoundly influences the gut microbiome and host immune response. Our research focuses on the whole genome sequencing and comparative genomic analysis of these Brucella strains to understand their influence on gut microbiome composition and immune dysregulation. Methods: using the Brucella melitensis strains CMCC55210 and its naturally attenuated variant CMCC55210a as models. Biochemical identification tests and in vivo experiments in mice verified characteristics of the strain. In order to understand the mechanism of attenuation, we then performed de novo sequencing of these two strains. Results: we discovered notable genomic differences between the two strains, with a key SNP mutation in the manB gene potentially altering LPS structure and influencing the gut microbiome-immune system interaction. This mutation might contribute to the attenuated strain's altered impact on the host's gut microbiota and immune response, offering insights into the mechanisms of immune dysregulation linked to gut microbiome imbalance. Furthermore, we explore that manipulating the Type I restriction-modification system in Brucella can significantly impact its interaction with the gut microbiome, consequently affecting the host's immune system. Conclusions: this study not only contributes to understanding the complex relationship between pathogens, the gut microbiome, and the immune system but also opens avenues for innovative therapeutic interventions in inflammatory diseases driven by microbial and immune dysregulation.